Connection between performance and body sway/morphology in juvenile Olympic shooters - Mon, D.; Zakynthinaki, M. S.; Calero, S. (Journal of Human Sport & Exercise, 2019)
The objective of the study was to examine, via use of a simple specific test, the correlation between body sway and performance in Juvenile Olympic shooters, to compare the differences in body morphology between different shooting modalities and to know if the anthropometric profile of a shooter influences performance. 38 national level juvenile shooters (24 pistol and 14 rifle) who competed at a pistol and air rifle Young Promises Spanish Championship participated in the study. Body sway (measured in terms of movements of the Centre of Pressure (COP): maximum displacements, maximum and minimum average velocities, rotation angles and total areas) and anthropometric data (age, height and weight) were recorded under competition conditions during shooting simulations. Performance was measured in terms of average points per shot. The variables of stress and experience before competition were also considered. The study was observational and descriptive following a cross-sectional design. The results showed that, in the juvenile category, rifle shooters perform better than pistol shooters, but pistol shooters have less body sway. Performance was found to be statistically related to COP displacements, only in pistol shooters. Body weight was found to be related to body sway but not with performance. Body height was found to be related neither with body sway, nor with performance No anthropometric differences have been found to exist between the different modalities (pistol and rifle).